A Survey: Attacks against RPL network in IoT - Yuvarani, S (International Journal of Computer Sciences and Engineering, 2025)
The security is the most important issue in Internet of Things (IoT) nowadays. In this paper we discuss the attacks against Routing Protocol for Low power and Lossy Networks (RPL).The IoT contains the constrained devices which are limited in resources like limited power, memory and processing capabilities. Healthcare, Home appliances, Transport, Social Networking, Defences, Banking are some examples of IoT applications. For this purpose the new protocol is designed called RPL. The RPL is a network layer protocol .The RPL is a leight weight distance vector protocol. In IoT to provide the security and privacy is challenging when the devices are connected to the lossy networks. In this paper the research is focus on the attacks against the RPL.